Franciscana, Pontoporia blainvillei, stranding records from systematic beach surveys, opportunistic and incidental capture reports at theRío Negro Estuary, Patagonia, Argentina (2003 – 2023) - Iñiguez Bessega, Miguel A. (2024)
Detailed here are records of 34 franciscanas (Pontoporia blainvillei) that stranded, including nine rescued alive and returned to sea, from the Río Negro Estuary, Patagonia, Argentina, between 2003 and 2023. The years with the highest stranding records were 2014 and 2020 (n = 6/ each). Autumn and winter/spring were the seasons with the lowest and highest number of strandings, respectively. These strandings comprised 15 females, six males, and 13 unknowns. Total body length offemales ranged from 64 to 155 cm and for males ranged from 70 to 138 cm. Five of the strandings involved calves and occurred within the birthing periods previously reported for the speciesat the Río Negro Estuary. A complete necropsy was performed on three animals. One showed multifocal pneumonic lesions from which Klebsiella pneumoniae was isolated and identified microbiologically. In a second specimen, Pseudomonas sp. and coagulase-negative Staphylococcus sp. were identified, and in a third individual tuberculosis caused by a memberof the Mycobacterium tuberculosis complex was identified. Despite these results, it was not possible to be certain that they were the causes of death of these three individuals. Three franciscanas had beak deformities. A total of 79 otoliths representing 41 specimens of white croaker (Micropogonias furnieri) were found in one stomach content analyzed. Elevenfranciscanas showed signs of having been bycaught (four with net marks, four entangled in gillnets or reported by the fishermen who bycaught them (n=3)). This is the first report of franciscanaentanglements in sport fishing gear at the Río Negro Estuary. This paper provides information highlighted as important by the International Whaling Commission Conservation ManagementPlan for franciscana, and contributes to knowledge of the species in the Franciscana Management Area IVe.